A case of acute mercury vapour poisoning - Eastmond, C. J. (1975)
A case is reported of a research chemist who was briefly exposed to a high concentration of mercury vapour and who developed symptoms of systemic poisoning, but who had a normal urinary excretion of mercury. This latter is not considered to refute the diagnosis. The literature is briefly reviewed.